2018
DOI: 10.3892/ol.2018.8678
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of α3, β3 and γ2 chains of laminin‑332 is associated with poor prognosis in pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDA) is a worldwide health problem. Early diagnosis and assessment may enhance the quality of life and survival of patients. The present study investigated the potential correlations between the gene and protein expression of laminin-332 (LM-332 or laminin-5) and clinicopathological factors as well as evaluating its influence on the survival of patients with PDA. The expression of LM-332 subunit mRNAs in pancreatic carcinoma specimens from 37 patients was investigated by rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Furthermore, there was no investigation into the reason that the three LM-332 subunits α3, β3 and γ2, exerted different effects on PDAC cells, nor was there any investigation into the underlying mechanism of this finding, which will form the main focus of future research. In our previous research, enhanced expression of LAMA3, LAMB3 and LAMC2 were confirmed with tissue analysis (17,20). The increased expression levels of the three subunits of LM-332 were significantly associated with worse differentiation, deeper depth of invasion, a more advanced stage and shorter survival time in PDAC.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Furthermore, there was no investigation into the reason that the three LM-332 subunits α3, β3 and γ2, exerted different effects on PDAC cells, nor was there any investigation into the underlying mechanism of this finding, which will form the main focus of future research. In our previous research, enhanced expression of LAMA3, LAMB3 and LAMC2 were confirmed with tissue analysis (17,20). The increased expression levels of the three subunits of LM-332 were significantly associated with worse differentiation, deeper depth of invasion, a more advanced stage and shorter survival time in PDAC.…”
Section: Discussionmentioning
confidence: 55%
“…It was recently demonstrated that upregulation of LAMA3 is associated with poor prognosis in PDAC (17). In our previous study, the increased expression of LAMA3 was significantly associated with worse differentiation, deeper depth of invasion, more advanced stage, and shorter survival time in PDAC (17). In addition, LAMA3 expression was assessed in human PDAC cells and it was revealed that it was significantly higher in PANC1 cells than in H6C7 cells.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations